Comparative studies on histomorphology of tensor tympani muscle in carnivores and small ruminants - Ziya ÖZCAN (Eurasian Journal of Veterinary Sciences)
In this study, the histomorphology of tensor tympani muscle, one of the muscle in the middle ear, was comparatively studied in carnivores and smail ruminants at various age groups. The massiveness of muscles in different size and weigh, thin and thick type content of muscle fibers, and additionally the amount of fat cells among the muscle fibres were the striking features between these two species. In smail ruminants, the myofibrils in a muscle fibre were showed a straight course at all age groups, while those in a thick muscle fibre in carnivores displaid a spiral arrangement, related to the age of animal Regarding the differences found histomorphologically, it is thought whether a correlation existed between the high/low sensitivity in hearing and the structure, in these species.